Popular music exhibitions in Portugal: practices of representation from 2007 to 2013 - Mota, Alcina Maria de Oliveira Cortez (2015)
This thesis focuses on the representation of Popular Music in museums by mapping, analyzing, and characterizing its practices in Portugal at the beginning of the 21st century. Now that museums' ability to shape public discourse is acknowledged, the examination of popular music's discourses in museums is of the utmost importance for Ethnomusicology and Popular Music Studies as well as for Museum Studies. The concept of 'heritage' is at the heart of this processes. The study was designed with the aim of moving the exhibiting of popular music in museums forward through a qualitative inquiry of case studies. Data collection involved surveying pop-rock music exhibitions as a qualitative sampling of popular music exhibitions in Portugal from 2007 to 2013. Two of these exhibitions were selected as case studies: No Tempo do Gira-Discos: Um Percurso pela Produção Fonográfica Portuguesa at the Museu da Música in Lisbon in 2007 (also Faculdade de Letras, 2009), and A Magia do Vinil, a Música que Mudou a Sociedade at the Oficina da Cultura in Almada in 2008 (and several other venues, from 2009 to 2013). Two specific domains were observed: popular music exhibitions as instances of museum practice and museum professionals. The first domain encompasses analyzing the types of objects selected for exhibition; the interactive museum practices fostered by the exhibitions; the concepts and narratives used to address popular music discursively, as well as the interpretative practices they allow. The second domain, focuses museum professionals and curators of popular music exhibitions as members of a group, namely their goals, motivations and perspectives. The theoretical frameworks adopted were drawn from the fields of ethnomusicology, popular music studies, and museum studies. The written materials of the exhibitions were subjected of methods of discourse analysis methods. Semi-structured interviews with curators and museum professional were also conducted and analysed. From the museum studies perspective, the study research suggests that the practice adopted by popular music museums largely matches that of conventional museums. From the ethnomusicological and popular music studies stand point, the two case studies reveal two distinct conceptual worlds: the first exhibition, curated by an academic and an independent researcher, points to a mental configuration where popular music is explained through a framework of genres supported by different musical practices. Moreover, it is industry actors such as decision makers and gatekeepers that govern popular music, which implies that the visitors' romantic conception of the musician is to some extent dismantled; the second exhibition, curated by a record collector and specialist, is based on a more conventional process of the everyday historical speech that encodes a mismatch between “good” and “bad music”. Data generated by a survey shows that only one curator, in fact that of my first case study, has an academic background. The backgrounds of all the others are in some way similar to the curator of the second case study. Therefore, I conclude that the second case study best conveys the current practice of exhibiting Popular Music in Portugal.